2002
DOI: 10.1103/physreve.66.036306
|View full text |Cite
|
Sign up to set email alerts
|

Saltating motion of a bead in a rapid water stream

Abstract: This paper experimentally and numerically investigates the two-dimensional saltating motion of a single large particle in a shallow water stream down a steep rough bed. The experiment is prototypical of sediment transport on sloping beds. Similar to the earlier experimental results on fine particles entrained by a turbulent stream, we found that most features of the particle motion were controlled by a dimensionless shear stress (also called the Shields number) N(Sh) defined as the ratio of the bottom shear st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
102
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 55 publications
12
102
1
Order By: Relevance
“…When considering resuspension from a sediment layer, additional forces are involved due to interparticle collisions and cohesion. The upward ͑or streamwise͒ force resulting from the momentum transfer when two sediment grains collide scales as 10 p 0 d 2 , whereas cohesive forces are known to be significant for fine sediments only, 31 typically with d Շ 30 m, significantly smaller than the particles considered in this article. In the present context, therefore, we expect forces of the form F L and F B to remain the dominant terms in the force balance for resuspension.…”
Section: Resuspension Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…When considering resuspension from a sediment layer, additional forces are involved due to interparticle collisions and cohesion. The upward ͑or streamwise͒ force resulting from the momentum transfer when two sediment grains collide scales as 10 p 0 d 2 , whereas cohesive forces are known to be significant for fine sediments only, 31 typically with d Շ 30 m, significantly smaller than the particles considered in this article. In the present context, therefore, we expect forces of the form F L and F B to remain the dominant terms in the force balance for resuspension.…”
Section: Resuspension Characteristicsmentioning
confidence: 98%
“…[5][6][7][8][9][10][11] Using artificial micron-sized sediment ͑with relative density 1.05͒, Kaftori et al 7 showed particle transport, resuspension, and deposition to be largely controlled by the action of streamwise coherent wall structures identified as funnel-type vortices ͑i.e., taking the shape of an expanding spiral, wound around a funnel laid sideways in the direction of the flow͒. Further experiments, 9 with improved resolution of the fluid flow field and particle motions in the near-wall region, have extended this study to consider natural sediments.…”
Section: Introductionmentioning
confidence: 99%
“…(12b), with Q /Q 0 = 1 assumed, is consistent with experimental data (using hydraulically rough bedforms). 19,20,37 In particular, Chiew and Parker, 20 using natural sediments with d p between 500 and 2700 μm and streamwise bed slopes in the range 0 ≤ β/β r ≤ 0.85, found good agreement with measurements of u * ,c /u * ,c,0 obtained from a steady closed-conduit flow, where the critical bed shear velocity (u * ,c ) was estimated using a standard empirical formulation based on the streamwise time-averaged mean flow velocity. Figure 10 shows the measured values ofû b,c /û b,c,0 plotted against β/β r , with each sediment type indicated by a different data symbol (see caption).…”
Section: B Critical Conditions For Sediment Movementmentioning
confidence: 99%
“…More references can be found in recent reviews on Aeolian transport (Durán et al 2011, Kok et al 2012, Valance et al 2015. Saltation may also be relevant in aquatic flows (Fernandez Luque & van Beek 1976, Abbot & Francis 1977, Ancey et al 2002, Niño & García 1998. The differences in saltation occur because of the difference in the mass density of the material of the grains relative to that of air and water and the differences in the kinematic viscosities of the two fluids.…”
Section: Introductionmentioning
confidence: 99%